DYNAMICS OF FREQUENCY AND PECULIARITIES OF THE STRUCTURE OF CONGENITAL MALFORMATIONS IN SOUTH UKRAINE (MONITORING STUDY) - Lanovenko, O. (International Journal of Medicine and Medical Research, 2021)
Background. In Ukraine, the unfavorable demographic situation makes monitoring of the birth rate of children with congenital malformations urgent issue to identify regional features of epidemiology and develop methods for prenatal diagnosis and prognosis. Objective. Objective of this study is to characterize the frequency dynamics, to identify structural features of congenital malformations of newborns in Kherson region over a 20-year period (2000-2019) and to compare the prevalence of various nosological forms of malformations in the region, in Ukraine and in European countries. Methods. Research methods: epidemiological, medical-statistical. Results. In Kherson region, the average frequency of congenital malformations over the past 20 years is: for newborns – 31.57±1.25‰; for live births – 31.38±1.11‰; for stillborns – 197.7±0.65 per 10,000. In the structure of defects, cardiovascular malformations are leading (31.77%), musculoskeletal malformations (25.14%), genital malformations (17.5%). Increased prevalence of developmental anomalies in the region is mainly associated with an increase in the frequency of model malformations recorded by EUROCAT (r=0.69, p<0.05). The increase in the total frequency of congenital malformations is caused by increased number of births of children with cardiovascular defects (by 4.67‰), genital defects (by 1.21‰), other congenital malformations (by 1.55‰), multiple malformations (by 0.37‰). Conclusion. Monitoring results showed an increase in congenital malformations incidence in Kherson region over a 20-year period by 7.94‰ possibly caused by population decline due to negative natural and mechanical growth. The prevalence of hereditary defects is at the same level. The frequency of some nosological forms significantly exceeds in the region compare to that in Ukraine and Europe: cardiovascular defects – in 1.5 times, genital malformations – in nearly 3 times, musculoskeletal defects – almost twice.